DESAIN DAN IMPLEMENTASI SISTEM PENYUSUNAN JADWAL ASISTEN PRAKTIKUM PADA LABORATORIUM KOMPUTER SEKOLAH TINGGI MANAJEMEN INFORMATIKA DAN KOMPUTER (STMIK) PRADNYA PARAMITA MALANG MENGGUNAKAN ALGORITMA GENETIKA - Wahyu Widarti, Dinny; Safiroh Utsalina, Dwi; Trisno Sami, Sri Esti (JURNAL TEKNOLOGI INFORMASI: Teori, Konsep, dan Implementasi, 2011)
Scheduling at the College of Information Management and Computer Pradnya Paramita Malang (STIMATA) is a routine that is always done at every turn of the semester. One of the scheduling assistant in the laboratory. Currently scheduling lab assistant in STIMATA is still done manually. Students who wish to register as a lab assistant, must submit a schedule of lectures and lab courses specialization are available. Coordinator / Lab administration then choose which of the candidates for an assistant who register to be placed in the laboratory according to the specialty. However, if the schedule constraints often occur in conjunction with the lab assistant lecture schedule as a student STIMATA. Therefore we need a system that can automatically schedule the deployment assistant fast and easy and can solve problems in the manufacturing schedule. Genetic algorithm is a method often used in the search for the best solution of the many solutions, especially in the case of scheduling. Therefore, it is expected through the facility / application might help solve the problems at the lab assistant schedule preparation STIMATA as a case study in to provide the optimum solution using a genetic algorithm. Key words: Schedule, Assistant, Genetic Algorithm.